Neurological Complications of Intrathecal Methotrexate in Children: A Prospective Study: Neurological Effects of Intrathecal Methotrexate - Shaheen, Hijab; Ruqayya Manzoor; Nuzhat Yasmeen; Zehra Batool; Muhammad Wasim Khan; Nazia Rafique (Journal of University College of Medicine and Dentistry, 2025)
Objective: To determine the neurological complications of Intrathecal Methotrexate (MTX) in pediatric patients receiving treatment for childhood malignancy in a tertiary care hospital of Islamabad, Pakistan. Methodology: This prospective observational study was conducted at the Pediatric Oncology Department of the Children’s Hospital, Pakistan Institute of Medical Sciences (PIMS) Islamabad from January to December 2024. During the study period, 96 patients aged 1–13 years received 796 intrathecal (IT) MTX administrations under aseptic conditions. We recorded both minor and major neurological complications occurring within 3 days following administration of IT MTX. The minor complications were defined as headaches, dizziness, or mild sensory disturbances, while major complications comprised serious neurological effects such as seizures, paralysis, or profound cognitive impairments. Results: The mean age of patient was 5.37 years, with 56.3% aged 3–5 years and 68.8% being male. Acute Lymphoblastic Lymphoma (ALL) was the primary diagnosis in 91.7% of patients, with 61.5% receiving a 12 mg dose of IT MTX. Neurological side effects were reported in 28.9% (n=231) of IT MTX administrations. No major neurological complications such as seizures or paralysis were observed. Minor side effects included fever (5.0%), nausea (4.5%), vomiting (4.1%), and dizziness (3.8%). Most symptoms manifested within 24 hours and were treated within 7 days. Conclusion: IT MTX plays an important role in pediatric oncology, but its neurotoxic potential requires close monitoring and management especially in children receiving IT chemotherapy for therapeutic or prophylactic purposes.